Pengaruh Opinion Shopping dan Disclosure terhadap Opini Audit Going Concern Dimoderasi Prior Opinion - Anggie Widiasari; Rida Perwita Sari (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This research goal is to prove the effect of opinion shopping and disclosure on the going concern opinion with prior opinion as moderating variable. The population of this research is companies in sector finance that listed in BEI. The sample is selected with purposive sampling technique of 100 companies. The analysis technique used is SEM based on Partial Least Square (PLS) with SmartPLS 3.0 software. Based on the results, this reasearch found that there is effect of opinion shopping on going concern audit opinion, but there is no effect of disclosure on going concern audit opinion. The next result is there is moderating effect of prior opinion on the effect of opinion shopping on the going concern audit opinion, but there is no moderating effect of prior opinion on the effect of disclosure on the going concern audit opinion.